2002
DOI: 10.1103/physrevlett.88.056802
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Fractional Quantum Hall Edges

Abstract: We study the interplay of interaction, confining potential and effects of finite temperature at the edge of a quantum Hall liquid. Our exact diagonalization calculation indicates that edge reconstruction occurs in the fractional quantum Hall regime for a variety of confining potential, including ones that correspond to a "sharp" edge. Our finite temperature Hartree-Fock calculation for integer quantum Hall edges indicates that reconstruction is suppressed above certain temperature. We discuss the implication o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
165
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(179 citation statements)
references
References 9 publications
12
165
2
Order By: Relevance
“…35,41 The results in Fig.1(b) shows that the energies of the edge spectrum from the Jacks are consistent with the exact diagonalization with a high accuracy. The largest leakage is in the order of 10…”
Section: ∆M =supporting
confidence: 66%
See 1 more Smart Citation
“…35,41 The results in Fig.1(b) shows that the energies of the edge spectrum from the Jacks are consistent with the exact diagonalization with a high accuracy. The largest leakage is in the order of 10…”
Section: ∆M =supporting
confidence: 66%
“…42 One possible reason of this discrepancy is electronic density reconstruction at the edge of FQH liquid. 41,43 The edge reconstruction introduces additional non-chiral edge modes that do not correspond to the bulk topology which break down the universality. From a simple electrostatic analysis of the 2DEG in semiconductor heterostructure as did in Ref.…”
Section: Edge Modes Near Reconstructionmentioning
confidence: 99%
“…The edge reconstruction is also important in the fractional regime as it is determined by the interplay of electron-electron interaction in the fractional regime, the single-particle electrostatic edge potential (or antidot potential), and effects of finite temperature. A recent numerical prediction [110] on edge reconstruction in the fractional regime has been linked to experimental results [111] on the microwave conductivity of two-dimensional electron systems with an array of antidots. More systematic studies on the edge reconstruction are required to understand excitations of an antidot in both the integer and fractional regimes.…”
Section: Density-functional Studies On the Compressibility Of Antidotmentioning
confidence: 99%
“…Previous numerical studies 4,5 have suggested that the phenomenon of edge reconstruction can be understood as an instability of the original edge mode described by the CLL theory. This instability occurs as a result of increasing curvature of the edge spectrum as the edge confining potential softens.…”
mentioning
confidence: 99%